Layered Landscapes: Constructing Form and Meaning from the Sketches of Arthur Erickson. CANADIAN ARCHITECTURAL ARCHIVES, UNIVERSITY OF CALGARY - Gourlie, Michael (Archivaria, 2014)
Layered Landscapes: Constructing Form and Meaning from the Sketches of Arthur Erickson. CANADIAN ARCHITECTURAL ARCHIVES, UNIVERSITY OF CALGARY. Mounted at the Nickel Galleries, Taylor Family Digital Library, University of Calgary. October 2013 to January 2014. Curated by LINDA FRASER and GEOFFREY SIMMINS.